Analisis Mutu Pelayanan Rawat Jalan Berdasarkan Waktu Tunggu Pemeriksaan Di Poli Umum Puskesmas Bontomarannu - Istiqamah, Nurul Fajriah; Dian Anggraeni Rachman; Andi Atssam Mappanyukki; Wahyudin (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2024)
According to Law of the Republic of Indonesia No. 36 of 2009, article 1 paragraph 11 means that health services are a form of activities that have become a unit and have a relationship and are carried out continuously. The purpose of this study is to find out the analysis of service quality based on the waiting time for examinations at the Bontomarannu Health Center general poly. The research method used observation with a cross-sectional research design with a quantitative approach. The population in this study is the average number of outpatients at the Bontomarannu Health Center every year in the last three years as many as 9,375 people. The sample in this study was 95 people using the Axial Sampling technique. Based on the results of the study, it is known that the average length of outpatient examination at the general polyclinic of the Bontomarannu Health Center for new patients is 6.95 minutes and 5.23 minutes for old patients, the service at the public poly is of high quality and is in accordance with the service standards set by the Ministry of Health regarding the length of examination at the general polyclinic for both new and old patients, which is 10 minutes